Thermoacoustic and Ultrasonic Characterization of Aqueous Solutions of Anti Diabetic drug and Plant Extracts - Manisha N Dhanorkar,; A. B. Dhote, (The Bioscan, 2025)
The present study investigates the thermoacoustic and ultrasonic properties of aqueous solutions of Glimepiride and Aloe Vera extract, two potential anti-diabetic agents, at varying concentrations and temperatures (298.15 K, 303.15 K, and 308.15 K). Using ultrasonic interferometry, density, and viscosity measurements, key acoustic and thermodynamic parameters such as ultrasonic velocity, adiabatic compressibility, intermolecular free length, specific acoustic impedance, and relaxation time were evaluated. The results indicate that Glimepiride exhibits stronger solute-solvent interactions, as evidenced by higher ultrasonic velocity, lower adiabatic compressibility, and reduced intermolecular free length, suggesting enhanced molecular packing and structural stability. Conversely, Aloe Vera extract demonstrates greater molecular dispersion and hydration effects, as indicated by lower ultrasonic velocity and higher compressibility. Temperature-dependent variations in these parameters provide insights into solubility, stability, and bioavailability, which are crucial for pharmaceutical formulations. This study highlights the significance of thermoacoustic characterization in optimizing drug-excipient interactions for improved therapeutic efficacy.